PRIMARY MEDIASTINAL YOLK SAC TUMOR: A RARE CASE - Fitri Dewi Ismida; Budi Yanti (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Background. Yolk sac tumor is a subtype of germ cell tumor which is highly malignant. Mediastinal Yolk sac tumor is also an extragonadal germ cell tumor which is extremely rare and is common in children and young adults. We report a case of a Yolk Sac Tumor in the anterior mediastinum in a 21-year-old male patient.Case. A case of Yolk Sac Tumor in a 21-year-old man with complaints of shortness of breath and chest pain experienced for ± 2 weeks. The CT scan showed the soft tissue with high-density thorax in the anterior mediastinum. The Levels of Alpha Feto Protein (AFP) 2,000 ng / mL and Beta-Human Chorionic Gonadotropin (B-HCG) 1.20 mIU / mL. Macroscopically, it appears brownish-gray tissue with a volume of 0.5 ccs. Typical histopathological examination reveals a Yolk Sac tumor.Conclusion. Yolk Sac Tumor as a Mediastinal primary tumor is a rare tumor. The diagnosis must be made not only based on histopathological examination but also based on the patient's age and elevated serum alpha-fetoprotein (AFP) and Beta-Human Chorionic Gonadotropin (B-HCG). Despite there is modern chemotherapy, the prognosis for these tumors is highly poor.Keywords . Yolk sac tumor, mediastinum, germ cell.